Subspecialty training in Europe: a report by the European Network of Young Gynaecological Oncologists. Issue 4 (24th December 2020) - Lanner, Maximilian; Nikolova, Tanja; Gutic, Bojana; Nikolova, Natasha; Pletnev, Andrei; Selcuk, Ilker; Vlachos, Dimitrios-Efthymios; Razumova, Zoia; Bizzarri, Nicolò; Theofanakis, Charlampos; Lepka, Piotr; Kahramanoglu, Ilker; et al.
Abstract : Background: ESGO (European Society of Gynaecological Oncology) and partners are continually improving the developmental opportunities for gynaecological oncology fellows. The objectives of this survey were to evaluate the progress in the infrastructure of the training systems in Europe over the past decade. We also evaluated training and assessment techniques, the perceived relevance of ENYGO (European Network of Young Gynaecological Oncologists) initiatives, and unmet needs of trainees. Methodology: National representatives of ENYGO from 39 countries were contacted with an electronic survey. A graduation in well/moderately/loosely-structured training systems was performed. Descriptive statistical analysis and frequency tables, as well as two-sided Fisher's exact test, were used. Results: National representatives from 33 countries answered our survey questionnaire, yielding a response rate of 85%. A national fellowship is offered in 22 countries (66.7%). A logbook to document progress during training is mandatory in 24 (72.7%) countries. A logbook of experience is only utilized in a minority of nations (18%) for assessment purposes. In 42.4% of countries, objective assessments are recognized. Trainees in most countries (22 (66.7%)) requested additional training in advanced laparoscopic surgery. 13 (39.4%) countries have a loosely-structured training system, 11 (33.3%) a moderately-structured training system, and 9 (27.3%) a well-structured training system. Conclusion: Since the last publication in 2011, ENYGO was able to implement new activities, workshops, and online education to support training of gynaecological oncology fellows, which were all rated by the respondents as highly useful. This survey also reveals the limitations in establishing more accredited centers, centralized cancer care, and the lack of laparoscopic training.